LINGUO-STYLISTICS OF HORROR IN E. A. POE’S SHORT STORIES - Antonyan, Zaruhi (Armenian Folia Anglistika, 2024)
Horror is a genre of science fiction which is intended to, or has the capacity to frighten, scare or disgust the readers by inducing feelings of horror and terror. This piece of fiction in prose of variable length also shocks and startles the readers inducing feelings of repulsion or loathing through creating a frightening atmosphere. Horror is frequently supernatural, though it can be non-supernatural. Often the central menace of a work of horror fiction can be interpreted as a metaphor for the larger fears of a society. The present investigation of horror in E. A. Poe’s short stories through the linguo-stylistic and case study methods of analyses aims to disclose the very distinct role of horror fiction in the perspective of human emotions – a kind of “mediator” between the world and its reflection in the language. The results show that emotions as a psychological, physiological and philosophical phenomenon verbally reproduce the emotional attitude of the person towards the world, that emotions are contained, fixed, expressed and indicated in utterances in the form of ideas – and as such – emotions are a perfect object of linguo-stylistic study.
Keywords: emotions; fear; horror fiction; Poe; stylistic devices; expressive means